A new system formulation for the tolerance analysis of overconstrained mechanisms. (April 2015) - Dumas, A.; Gayton, N.; Dantan, J.-Y.; Sudret, B.
Abstract: The goal of tolerance analysis is to verify whether design tolerances enable a mechanism to be functional. The current method consists in computing a probability of failure using Monte Carlo simulation combined with an optimization scheme called at each iteration. This time consuming technique is not appropriate for complex overconstrained systems. This paper proposes a transformation of the current tolerance analysis problem formulation into a parallel system probability assessment problem using the Lagrange dual form of the optimization problem. The number of events being very large, a preliminary selective search algorithm is used to identify the most contributing events to the probability of failure value. The First Order Reliability Method (FORM) for systems is eventually applied to compute the probability of failure at low cost. The proposed method is tested on an overconstrained mechanism modeled in three dimensions. Results are consistent with those obtained with the Monte Carlo simulation and the computing time is significantly reduced. Abstract : Graphical abstract: Abstract : Highlights: A tolerance analysis problem is transformed into a system reliability problem. The Lagrange dual form of the optimization problem is written. The FORM method for systems is applied to solve the system reliability problem. The proposed procedure is detailed on an academic example. The proposed procedure is applied on an industrial case with success.